Understanding the income gradient in college attendance in Mexico: The role of heterogeneity in expected returns - Katja Maria Kaufmann (Quantitative Economics, 2014)
Differences in college enrollment between poor and rich are striking in Latin America. Explanations such as differences in college preparedness and credit constraints have been advanced. An alternative explanation could be differences in information sets between poor and rich, for example, about career opportunities, translating into different expected returns to college. Poor people might expect low returns and thus decide not to attend or they might face high (unobserved) costs that prevent them from attending despite high expected returns. I use data on people's subjective expectations of returns to address this identification problem. I find that poor individuals require higher expected returns to be induced to attend college than individuals from rich families. Testing predictions of a model of college attendance shows that poor individuals are particularly responsive to changes in direct costs, which is consistent with them being credit constrained. Performing counterfactual policy experiments, I find that a sizeable fraction of poor individuals would change their decision in response to a reduction in direct costs and that these individuals at the margin have expected returns that are as high or higher than the individuals already attending college.
Keywords: 330; Schooling choice; credit constraints; subjective expectations; marginalreturns to schooling; local instrumental variables approach; Mexico